(untitled) (JURNAL ADMINISTRASI PUBLIK, 2022)
Mining is an activity carried out by mining entrepreneurs with the aim of obtaining mining goods and profits from mining products. The reality is that the life of the community around the mine, such as in Batu Putih Bawah Village, Ranowulu District, Bitung City, is still less accepting of mining, there are still people who do not agree with mining. This research was conducted on April 27, 2021. The purpose of this study is to describe the Impact of Permit Mining for the Community in Batu Putih Bawah Village, Ranowulu District, Bitung City. The research method used is qualitative research methods, as well as data collection techniques carried out in this study through interviews, observation and documentation. The conclusion drawn from this study is that researchers found differences in perceptions or responses to information from both the mining company (company management), the government around the mine, the community who work as mining workers and people who are not mine workers. as follows, (1) the impact The positive things that occur are, increasing community income, increasing job opportunities and job opportunities for local communities, especially for people in Batu Putih Bawah Village, increasing program assistance from mining companies as well as reducing unemployment and increasing spending on goods. and services. (2) The negative impacts that occur include environmental damage, such as deforestation, soil erosion, air pollution due to pollution and sedimentation of the remains of waste dumped into the sea which results in a decrease in fisherman catches, a decrease in farmers’ yields, an improvement in public health conditions in the area. Lower Batuputih Village. Keywords: Impact, Policy, Licensing, Mining